Efektivitas Bakteri Rumen Sapi Sebagai Dekomposer Pada Berbagai Media Pengomposan: Efektivitas Bakteri Rumen Sapi Sebagai Dekomposer Pada Berbagai Media Pengomposan - Wiyono; Daryanti; Dian Rahma Agustin (JURNAL ILMIAH AGRINECA, 2026)
This study aims to evaluate the effectiveness of bacteria from the cow rumen as decomposer agents (bioactivators) in the composting process of various types of organic waste media. The cow rumen contains a high population of cellulolytic microorganisms, thus potentially accelerating the breakdown of organic matter. The method used was a completely randomized design (CRD) with two treatment factors: (1) type of bioactivator composition (without bioactivator; a combination of cellulolytic bacteria, rhizomonas, and cow rumen; cellulolytic and substilis bacteria; rhizomonas bacteria and cow rumen; and only cow rumen bacteria) and (2) type of composting media (rice straw and corn waste). The parameters observed included odor, color, temperature, pH, composting time, water holding capacity, final weight, and moisture content of the compost. The results showed that the use of cow rumen bioactivators not only accelerated composting, but also increased pH and humus formation, resulting in higher water holding capacity and water content in both straw and corn waste compost. The use of cow rumen combined with Rhizomonas bacteria slows down the straw composting process.